FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN BADAN USAHA-BADAN USAHA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2010-2014 - Wirata Wirata; Werner Ria Murhadi; Endang Ernawati (Perpustakaan Universitas Surabaya, 2017)
Abstract This study aims to analyze the factors that influence dividend policy. Variable used in this research is firm size (SIZE), profitability (ROA), debt policy (DER), growth (GROWTH), and liquidity (CR). This study used sample Firms Sector Consumer Good Industry which distribute dividend annually during 2010- 2014 period are listed in the Indonesia Stock Exchange. The number of observations used in this study were 60 observations. The result showed that the Consumer Good Industry Sector, profitability and debt policy variable significant positive effect on dividend policy while, growth variable significant negative effect on dividend policy. However, firm size, and liquidity variable negative not significant effect on dividend policy. Keyword: Dividend Policy, Profitability, Debt Policy, Growth.